Corporate Liquidity Management in Emerging Economies under the Financial Constraints: Evidence from China - Fahmida Laghari; Ye Chengang; Ye Chenyun; Yiding Liu; Li Xiang (Discrete Dynamics in Nature and Society)
The main purpose of this article is to investigate the impact of the optimum level of cash holdings on corporate performance. Moreover, in this paper, the impact of financial constraints is tested as moderating factor between the relationship of cash holdings and corporate performance. The present study uses the system generalized method of moments (GMM) as the main estimation methodology. Using a sample of companies listed on stock exchanges of China, empirical pieces of evidence find that cash holdings-corporate performance relation is a nonlinear concave and depicts similar evidence for firms with financial constraints. The financially constrained firms maintain optimal cash holding at a higher level, which corresponds to debt rationing, difficulty to access financial markets, and the high cost of external finance. Moreover, propensity-score-matching depicts statistically significant differences in the level of cash holdings amid financially constrained and unconstrained firms. Finally, the difference-in-difference estimator shows that financial crisis affects less financially constrained firms due to low reliance on external financing.